韩素音在马来亚 = Han Suyin in Malaya - 张星虹 Zhang, Ina Xing Hong (2013)
伊丽莎白KC精梳机，更好地了解她的笔名韩素音，是世界著名的小说家和社会活动家。出生于中国，在欧洲训练，来到英属马来亚的欧亚医生和作家，她的第二任丈夫于1952年，居住，直到1964年。小一直说，然而，甚至是知道，她在该地区内，本研究希望她的经验，在马来亚一些启发。通过设置韩素音的12年在该地区逗留的背景下二战后的条件在马来亚和评估结构和机构之间的互动，本文旨在以探索三个方面，即（一）在韩素音ofher年影响（二）马来亚，马来亚社会作为一个坦率的和充满激情的知识分子，以及（c）本文可以帮助重建战后马来亚的历史强调韩素音对马来亚社会的影响，以换取她的贡献。 Elizabeth KC Comber, better known by her pseudonym Han Suyin, is a world-renowned novelist and social activist. Born in China and trained in Europe, the Eurasian doctor and writer arrived in British Malaya with her second husband in 1952 and resided till 1964. Little has been said, however, or indeed even known, of her period in the region , and this study hopes to shed some light on her experiences in Malaya. By setting Han Suyin's 12-year stay in the region against the backdrop of post-WWII conditions in Malaya and evaluating the interaction between structure and agency, this paper seeks to explore three areas, namely (a) the impact on Han Suyin of her years in Malaya, (b) her contributions in return to Malayan society as an outspoken and passionate intellectual , and (c) how this paper could help in reconstructing parts of the history of post-war Malaya by underscoring Han Suyin's influence on Malayan society. As part of this endeavor, this paper delves into Han Suyin's life in Malaya as a prominent cross-cultural intellectual, focusing in particular on the reactions of Han Suyin and her fellow intellectuals towards the powerful tide of anti-colonialism and "Merdeka" movement then surging throughout Malaya. This paper seeks to show that the 12 years Han Suyin spent in Malaya were an indispensable part of her life, a part that should not be overlooked in studies of Han Suyin. The research undertaken for this paper illustrates that Malaya was not a mere home of convenience for Han Suyin, for whom post-1949 Communist China would have been out of the question , but a country which grew to become a platform for personal growth , allowing her to flourish as a medical practitioner, creative writer and public figure. It was in Malaya that she embraced and fully identified with her Asian roots, matured as a writer and boldly transcended cultural , ethnical and ideological boundaries. In return, post-war Malaya drew strength from her writings as it fought to break free of its colonial fetters in the quest for independence. More importantly, by focusing not on Han Suyin the celebrated writer, but rather on Han Suyin the individual, this monographic study strives to provide insight into the workings of a mind so often engaged in reasoned contradictions and to furnish readers with a fresh angle from which to appreciate her interactions with members of varying social strata in Malaya, her unique views that were a product of her dual eastern and western upbringing and ultimately her personal value system, hence presenting a useful case in today' s study of both domicile and diasporic intellectuals in post-war Malaya and at the same time, adding a long-overdue chapter to the studies of Han Suyin on the 60th anniversary of her arrival in Malaya.